COMPREHENSIVE INVESTIGATION ON THE GEOTHERMAL ENERGY SECTOR IN MEXICO - Yashar Aryanfar; Jorge Luis García Alcaraz; Julio Blanco Fernández; Hasan Köten; Mohamed M. Awad (CT&F Ciencia, Tecnología & Futuro)
Factors such as fossilisation, diversification of energy resources, sustainable development, and energy security are attracting global attention for the development and expansion of renewable energy sources. Environmental issues arising from fossil fuel consumption are being addressed, but concerns remain about the renewability and availability of new energy sources. Mexico is one of the ten countries in the exploitation of geothermal energy, with a history of approximately five decades. This study examines Mexico's five major geothermal fields: Cerro Prieto, Los Azufres, Los Humeros, Las Tres Vírgenes, and Domo San Pedro. Currently, Mexico is working with international geothermal companies. However, there are more power plants and substantial cooperation to obtain this energy for industry and homes. This study is focused on the potential of geothermal exploitation in Mexico and its position worldwide after the introduction of geothermal energy in Mexico. Next, five geothermal fields are introduced in Mexico, and the potential and capacities of each are discussed. Finally, the future energy scenarios in Mexico are reviewed, with an emphasis on geothermal energy .